Rethinking Must-Carry and Retransmission Consent Regulation in the Digital Era - Alvarez, Clara Luz (Law, State and Telecommunications Review, 2020)
The emergence of new technological platforms to access online services and content have transformed the media landscape dramatically. They require policymakers to reexamine the decades-old regulations traditionally addressed to broadcasters and telecommunications providers. Must-carry, retransmission consent, and “carry one, carry all” rules in particular require reconsideration, if not reform. Must-carry regulation mandates cable and satellite pay TV providers to retransmit free-to-air broadcast programming. Such regulations have been adopted around the world, including the United States, Mexico, and France, the subjects of this article. Policymakers in these three countries have offered a variety of justifications for such rules, including the promotion of competition, local news and content, viewers´ rights, and content diversity. Recent data and case law, however, strongly suggest that emergent platforms to access online services and content undermine the standing justifications for must-carry, retransmission, and “carry one, carry all” rules. This Article argues that policymakers should consider other regulatory mechanisms to achieve the original reasons for such rules. The dramatic increase in the variety of devices (e.g., TV, tablet, mobile phones, smart TVs), service and content distributors (e.g., free-to-air TV, cable TV, internet), and service providers (e.g., broadcasters and “over-the-top” internet providers) strongly suggests that policymakers must reconsider the current approach. But any amendment to current regulation will depend on internet penetration and access to new video distribution platforms in a given geographic area. That is, without internet access, free-to-air TV might continue to be an important platform for service and content distribution.